TRAGEDI SAMPIT 2001 DAN IMBASNYA KE PALANGKA RAYA (Dari Konflik ke (Re)konstruksi) - Patji, Abdul Rachman (Jurnal Masyarakat dan Budaya, 2003)
This article discusses the 2001’s ethnical conflict between Madures and groups of the Dayak people in Central Kalimantan. The discussion about the Palangka Raya case, but the conflict itself is the impact of Sampit’s tragedy where the conflict firtsly emerge. This article focuses on how the government’s official of Palangka Raya together with other elements of population to manage the conflict and the Dayak efforts to reconstruct their social and ethnical traditions after the tragedy.